Salt-free and chrome-free tanning method and prepared tanned leather
Through the method of pre-tanning of bio-based bisaldehyde carboxylic acid and unsalt-leaching acid combined with iron salt tanning, the problems of insufficient tanning properties, chlorine-containing wastewater and unstable storage in traditional iron salt tanning methods are solved, and efficient, environmentally friendly and storage-resistant iron tanning leather production is achieved.
Patent Information
- Application Number
- CN202411917074.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The traditional iron salt tanning method has the problems of weak tanning properties, chlorine-containing wastewater, and iron-tanned leather is not easy to preserve, and is easy to harden and become brittle, which limits its widespread application.
The softened bare skin is pre-tanned by using bio-bialdehyde carboxylic acid, combined with unsalted acid and iron salt tanning. Through the covalent combination of bio-bialdehyde carboxylic acid and the dermal collagen amino group, a Schiff alkali structure is formed to prevent acid swelling, and the absorption and fixation of iron tanning agents are promoted during the iron tanning process, and a stable cross-linking network is constructed.
It significantly improves the tanning effect of iron tanning agent, reduces chloride ion emissions, extends the storage stability and service life of iron tanned leather, and improves the moisture and heat stability and storage resistance of leather.
Smart Images

Figure CN119530469A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leather tanning, in particular to a salt-free and chromium-free tanning method and the tanned leather obtained. Background Art
[0002] The traditional chrome tanning process involves two processes, pickling and chrome tanning, which inevitably leads to the discharge of a large amount of chlorine- and chromium-containing wastewater, and faces increasingly severe environmental protection challenges. The research and development of salt-free and chrome-free tanning technology has become a key issue that the leather industry needs to solve urgently. Non-chrome metal tanning technology has become a research hotspot due to its high compatibility with subsequent dyeing and finishing processes. In particular, iron salt tanning agents are considered to be an ideal choice to replace chrome tanning agents due to their advantages such as abundant reserves and low cost. However, the traditional iron salt tanning method still follows the process path of "first pickling, then iron salt tanning", which leads to three major problems in this technology: first, the tanning property is weak, second, chlorine-containing wastewater is generated, and third, iron-tanned leather is not easy to preserve and is easy to harden and become brittle. These problems seriously limit the widespread application of iron tanning technology. Therefore, the development of a salt-free and chrome-free tanning technology that can effectively solve the above problems and achieve low cost, high efficiency and environmental friendliness is of vital importance to promote the innovation and development of clean leather technology. Summary of the invention
[0003] In view of the problems existing in the above-mentioned background technology, the present invention aims to provide a salt-free and chromium-free tanning method and tanned leather which are eco-friendly, have excellent tannability and good storage resistance.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is: Using softened bare hides as raw materials, bio-based dialdehyde carboxylic acid pre-tanning, salt-free pickling and iron salt tanning are carried out in sequence; Wherein, based on the weight of the limed bare skin, the added amount of the bio-based dialdehyde carboxylic acid is 1wt%-5wt%; the added amount of the iron salt is 5wt%-30wt%.
[0005] Preferably, the softened bare hide comprises any one of softened sheep hide, softened goat hide and softened cow hide.
[0006] Preferably, the bio-based dialdehyde carboxylic acid comprises any one of dialdehyde sodium alginate, dialdehyde sodium carboxymethyl cellulose and dialdehyde carboxymethyl starch.
[0007] Preferably, the bio-based dialdehyde carboxylic acid pre-tanning is performed by infiltrating the raw material with the bio-based dialdehyde carboxylic acid for 30-360 minutes and then combining at 35-42° C. for 30-240 minutes.
[0008] Preferably, the salt-free pickling is performed by adjusting the pH of the reaction solution to 2.5-4.0 without using sodium chloride.
[0009] Preferably, the iron salt comprises iron sulfate or iron nitrate.
[0010] Preferably, the iron salt tanning is to use iron salt to penetrate the pre-tanned raw material for 60-300 minutes, add alkali to pH 3.5-4.5, and combine at 35-42°C for 60-180 minutes.
[0011] Preferably, the iron salt tanning process further contains a ligand, and the ligand comprises any one or more of sodium formate, sodium lactate, sodium tartrate and sodium citrate.
[0012] Preferably, the alkali extracting agent used in the alkali extracting comprises any one or more of sodium bicarbonate, sodium carbonate, magnesium oxide and automatic alkali extracting agent.
[0013] The invention also discloses tanned leather obtained by adopting any of the above-mentioned salt-free and chromium-free tanning technologies.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) Significantly improved environmental friendliness: The present invention realizes both salt-free pickling and chrome-free tanning, significantly reduces the emission of chloride ions, and solves the problem of chromium pollution from the source, thereby greatly reducing the impact of the leather industry on the environment and demonstrating excellent ecological and environmental protection performance.
[0015] (2) Improved tanning performance: The present invention cleverly combines biomass dialdehyde carboxylic acid tanning agent with iron salt for combined tanning, which significantly enhances the tanning effect of iron salt and greatly improves the wet heat stability of iron tanned leather, providing a tanning solution with superior performance for leather processing.
[0016] (3) Enhanced storage stability of iron-tanned leather: In view of the defects of traditional iron-tanned leather that is easy to age, harden and become brittle, the present invention effectively improves the aging resistance of iron-tanned leather, greatly enhances the storage stability and service life of iron salt tanned leather, and further broadens the application scope and market potential of iron-tanned leather. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a tanning principle diagram of an embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.It should be understood that these descriptions are exemplary only, and are not intended to limit the scope of the present invention.In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.Unspecified conditions in the embodiments are carried out according to the conditions of normal conditions or manufacturer recommendations.Reagents used or instruments that do not specify manufacturers are conventional products that can be purchased and obtained commercially.
[0019] The embodiment provided by the present invention is a salt-free and chrome-free tanning technology: Using softened bare hides as raw materials, bio-based dialdehyde carboxylic acid pre-tanning, salt-free pickling and iron salt tanning are carried out in sequence; Wherein, based on the weight of the limed bare skin, the added amount of the bio-based dialdehyde carboxylic acid is 1wt%-5wt%; the added amount of the iron salt is 5wt%-30wt%.
[0020] The traditional iron salt tanning method follows the process flow of "pickling first, then iron salt tanning". During the pickling process, the reason why the bare skin swells is that the acid combines with the collagen amino group, causing the amino group to be protonated and causing the skin collagen to carry a positive charge. Due to the repulsion between the charges, the bare skin swells significantly. In order to inhibit this acidic swelling phenomenon, it is usually necessary to add neutral salts. The mechanism of action of neutral salts is to increase the concentration of diffusible ions in the external solution, balance the osmotic pressure inside and outside the skin collagen, and promote the penetration of water molecules from the inside of the skin to the outside of the skin, thereby effectively inhibiting the expansion of the bare skin in the pickling solution. However, the introduction of neutral salts inevitably brings about the problem of the discharge of chlorine-containing wastewater, which increases the difficulty of wastewater treatment. In order to solve this problem, the applicant conducted a large number of experiments and found that the bare skin can be prevented from swelling due to acid by pre-tanning the softened bare skin with bio-based dialdehyde carboxylic acid during the pickling process. The principle is that bio-based dialdehyde carboxylic acid is a biomass material with both dialdehyde and carboxyl functional groups. The dialdehyde group can covalently bind to the amino group of skin collagen to form a Schiff base structure, which blocks the amino group to reduce the positive charge of bare skin and cross-links the bare skin collagen, thereby preventing bare skin acid swelling. Finally, safe salt-free pickling is achieved.
[0021] The tanning effect of traditional iron tanning is relatively limited, resulting in insufficient cross-linking and fixation of collagen fibers by iron tanning agents. The present invention innovatively introduces bio-based dialdehyde carboxylic acid to pre-tan softened bare skin. Additional carboxyl binding sites are successfully introduced by covalently bonding the dialdehyde groups in the bio-based dialdehyde carboxylic acid molecules to the amino groups in the skin collagen. In the subsequent iron tanning process, the carboxyl groups of the bio-based dialdehyde carboxylic acid can effectively promote the absorption and fixation of the iron tanning agent, thereby building a more stable and tough cross-linked network structure ( Figure 1 ), which significantly improved the tanning performance of iron tanning agents.
[0022] In addition, traditional iron-tanned leather is usually difficult to withstand the test of long-term storage and is prone to hardening and brittleness during storage. The reason is that, on the one hand, iron ions, as photocatalysts, will generate active free radicals that are destructive to collagen during storage, resulting in a decrease in leather performance; on the other hand, although Fe 3 + However, under the action of reducing components in leather, Fe 3+Will be reduced to non-tannable Fe 2+ , thus inducing the detanning phenomenon, further aggravating the aging of the leather. It is for the above reasons that the quality of tanned leather using iron salts as tanning agents in the prior art is poor and is not common. The present invention solves this problem for the first time and can significantly enhance the storage stability of iron-tanned leather. The key means is to combine the bio-based dialdehyde carboxylic acid pre-tanning with iron salt tanning for the first time. Specifically: the bio-based dialdehyde carboxylic acid uses polysaccharides as raw materials, which not only has a certain free radical scavenging ability, but can also effectively scavenge the active free radicals generated by iron-tanned leather during the storage process to avoid damage to the leather; and the carboxyl group in the bio-based dialdehyde carboxylic acid reacts with Fe 3+ A more solid closed structure is formed, making Fe 3+ Difficult to be reduced to Fe 2+ , thus effectively preventing the occurrence of detanning.
[0023] Based on the above theory, any bio-based aldehyde acid tanning agent containing both dialdehyde and carboxylic acid can achieve the effect of the present invention. For example, dialdehyde sodium alginate, dialdehyde sodium carboxymethyl cellulose and dialdehyde carboxymethyl starch. In the embodiment of the present invention, during the pre-tanning of bio-based dialdehyde carboxylic acid, the amount of bio-based dialdehyde carboxylic acid added is 1wt%-5wt% based on the weight of the limed bare skin. Within this addition amount range, the effect of the bio-based dialdehyde carboxylic acid is more fully exerted. If the addition amount is less than 1wt%, too little addition will lead to insufficient pre-tanning of the bare skin, making it difficult to avoid the acid swelling phenomenon during salt-free pickling, and at the same time making the subsequent iron tanning effect poor, and the storage performance cannot be significantly improved; if the addition amount is higher than 5wt%, first of all, the leather making cost will increase, and secondly, a large amount of bio-based dialdehyde carboxylic acid will be present on the surface of the tanned leather, making it difficult for the iron tanning agent to penetrate and surface binding will occur, thereby causing the tanned leather to not be "thoroughly tanned" and the subsequent iron tanning effect to decrease.
[0024] During the pre-tanning of bio-based dialdehyde carboxylic acid, the tanning agent penetration time, binding time, binding temperature, etc. are all conventional tanning parameters in the prior art, and can be adaptively selected by those skilled in the art according to the type of leather, the type of tanning agent, and the desired tanning effect, so they are not limited in the present invention and are only used as examples. For example, the penetration time of the dialdehyde carboxylic acid tanning agent in the raw material is 30-360 minutes, the binding temperature is 35-42°C, and the binding time is 30-240 minutes.
[0025] In some preferred embodiments, the softened bare hide is any one of softened goat hide, softened sheep hide and softened cow hide.
[0026] Salt-free pickling means that no sodium chloride is added when pickling the pre-tanned raw material. The pH of the specific acid solution and the reaction solution (i.e., bath solution) used are all commonly used in the art. For example, formic acid and / or sulfuric acid can be used to adjust the pH of the reaction solution to 2.5-4.0.
[0027] In some preferred embodiments, the commonly used iron salt tanning agent comprises iron sulfate and iron nitrate.
[0028] It is well known in the prior art that during iron salt tanning, in order to further improve the tanning effect, a ligand may be added simultaneously with the tanning, such as sodium formate, sodium lactate, sodium tartrate and sodium citrate.
[0029] In some optional embodiments, during iron salt tanning, the alkali extracting agent used for alkali extraction is an alkaline substance commonly used in the art, including any one or more of sodium bicarbonate, sodium carbonate, magnesium oxide and automatic alkali extracting agent.
[0030] In order to make the technical solution of the present invention clearer, a salt-free and chrome-free tanning method provided by the present invention is described in detail below through a plurality of specific embodiments and comparative examples.
[0031] In the following examples and comparative examples, the chloride ion concentration in the tanning wastewater is determined according to HJ / T 84-2016 "Determination of inorganic anions in water quality - ion chromatography". Iron-tanned leather is dyed and finished according to conventional processes to obtain iron-tanned crust leather, and its shrinkage temperature is measured using the MSW-YD4 shrinkage temperature instrument of Sunshine Electronics Research Institute; in addition, the softness of the crust leather is measured using the Gaotie GT-303 softness instrument, and the tensile strength and tear strength of the crust leather are measured using the Gaotie AI-7000S servo-controlled computer system tensile testing machine. In order to simulate the aging process, the crust leather is placed in a blast drying oven at 50°C for heat aging for 24 hours, turned over every 12 hours, and taken out after 24 hours to obtain the heat-aged crust leather.
[0032] Example 1 Add 120wt% water and 3wt% sodium dialdehyde alginate based on the weight of the limed bare hide to the softened cowhide, and after infiltration for 180min, combine at 42°C for 240min. Then, adjust the pH of the bath to 3.2 in a salt-free state. Then, change the bath, add 40wt% water, 16wt% iron sulfate and 4wt% sodium formate, and after infiltration for 180min, add alkali to the bath pH 4.0, combine at 42°C for 120min, and stand overnight to obtain iron tanned leather.
[0033] It was determined that the chloride ion concentration in the tanning wastewater in this embodiment was 0.2 g / L, the shrinkage temperature of the crust leather was 95.2°C, the softness was 8.1 mm, and the tensile strength was 14.5 N / mm 2 , tear strength is 45.4N / mm; after heat aging, the shrinkage temperature of the leather is 94.8℃, the softness is 8.0mm, and the tensile strength is 14.2N / mm 2 The tear strength is 44.8N / mm. The specific results are shown in Table 1.
[0034] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not use bio-based dialdehyde carboxylic acid to pre-tan the softened cowhide, but uses the traditional "salt pickling + iron tanning" method to tan the leather. The detailed process steps are: Add 120 wt% of water and 8 wt% of sodium chloride to the softened cowhide based on the weight of the limed bare hide, and adjust the pH of the bath to 3.2. Then remove 80 wt% of the acid solution, add 16 wt% of iron sulfate and 4 wt% of sodium formate, and after infiltration for 180 minutes, add alkali to the pH of the bath to 4.0, combine at 42°C for 120 minutes, and stand overnight to obtain iron tanned leather.
[0035] It was determined that the chloride ion concentration in the tanning wastewater in this embodiment was 13.4 g / L, the shrinkage temperature of the crust leather was 83.5°C, the softness was 6.8 mm, and the tensile strength was 13.8 N / mm 2 , tear strength is 42.1N / mm; after heat aging, the shrinkage temperature of the leather is 78.6℃, the softness is 5.6mm, and the tensile strength is 7.4N / mm 2 The tear strength is 12.6N / mm. The specific results are shown in Table 1.
[0036] According to the test results of Example 1 and Comparative Example 1, the following results can be obtained: Example 1 uses bio-based dialdehyde carboxylic acid for pre-tanning treatment, followed by salt-free pickling, and finally iron salt tanning. Due to the pre-tanning effect of bio-based dialdehyde carboxylic acid, the bare skin will not experience acid swelling during the pickling process without adding neutral salt, so the concentration of chloride ions in the tanning wastewater is extremely low, only 0.2g / L. These trace amounts of chloride ions mainly come from the salt used for pickling of raw hides and the residual salt in the chemical materials used in the leather preparation stage. In the subsequent iron salt tanning process, the additional carboxyl groups introduced by the bio-based dialdehyde carboxylic acid can form a coordination bond with the iron tanning agent, thereby forming a strong macromolecular cross-linked network between the collagen fiber network. This makes the shrinkage temperature of the iron-tanned crust leather as high as 95.2°C, the softness of the crust leather reaches 8.1mm, and the tensile strength reaches 14.5N / mm 2 , the tear strength reaches 45.4N / mm. In addition, due to the scavenging effect of bio-based dialdehyde carboxylic acid on active free radicals and Fe 3+ The iron tanned leather has no obvious detanning and deterioration after heat aging, and the shrinkage temperature is still as high as 94.8℃. The softness of the leather is 8.0mm and the tensile strength reaches 14.2N / mm 2 The tear strength reaches 44.8N / mm, indicating that the iron-tanned leather has not hardened and become brittle, and has excellent storage stability.
[0037] Comparative Example 1 adopted the traditional iron tanning method, that is, salt pickling treatment was first performed, followed by iron salt tanning. Since neutral salt was added during the pickling process to suppress the acid swelling of the bare skin, the chloride ion concentration in the tanning wastewater was as high as 13.4 g / L. In the subsequent iron salt tanning process, it was difficult for the iron tanning agent to form a stable cross-linked structure between the collagen fiber networks. Therefore, the shrinkage temperature of the obtained iron tanned leather was only 83.5°C, the softness was 6.8mm, and the tensile strength was 13.8N / mm 2 , the tear strength is 42.1N / mm. In addition, due to the generation of active free radicals and Fe 3+ The iron-tanned leather showed obvious detanning and deterioration after heat aging, with the shrinkage temperature dropping to 78.6℃, the softness dropping to 5.6mm, and the tensile strength dropping to 7.4N / mm. 2 , the tear strength dropped to 12.6N / mm. These results show that the traditional iron tanned leather hardened and became brittle after heat aging, and its storage stability was poor.
[0038] Through the analysis of the above embodiments and comparative examples, it can be clearly seen that the "bio-based dialdehyde carboxylic acid pre-tanning + salt-free pickling + iron salt tanning" method adopted in the present invention, compared with the traditional "salt pickling + iron salt tanning", not only shows significant advantages in ecology and tanning properties, but also the tanned leather has better storage resistance, which provides strong technical support for the clean transformation of the leather industry.
[0039] Table 1 Test results .
[0040] Example 2 Add 40wt% water and 1wt% sodium dialdehyde carboxymethyl cellulose based on the weight of the limed bare skin to the softened sheepskin, and after penetration for 30 minutes, combine at 38°C for 120 minutes. Then, adjust the pH of the bath to 2.5 in a salt-free state. Then, change the liquid, add 120wt% water, 5wt% ferric nitrate and 1wt% sodium lactate, penetrate for 300 minutes, extract the alkali to the pH of the bath to 4.5, combine at 35°C for 60 minutes, and stand overnight to obtain iron tanned leather.
[0041] It was determined that the chloride ion concentration in the tanning wastewater in this embodiment was 0.1 g / L, the shrinkage temperature of the crust leather was 88.7°C, the softness was 7.8 mm, and the tensile strength was 13.8 N / mm 2 , tear strength is 42.6N / mm; after heat aging, the shrinkage temperature of the leather is 87.9℃, the softness is 7.7mm, and the tensile strength is 13.2N / mm 2 , the tear strength is 41.9N / mm.
[0042] Example 3 Add 200wt% water and 5wt% dialdehyde carboxymethyl starch based on the weight of the limed bare hide to the softened goat, and after infiltration for 360min, combine at 35℃ for 30min. Then, adjust the pH of the bath to 4.0 in a salt-free state. Then, change the bath, add 200wt% water, 30wt% iron sulfate and 8wt% sodium tartrate, and after infiltration for 60min, use magnesium oxide to extract the alkali to the bath pH 3.5, combine at 42℃ for 180min, and stand overnight to obtain iron tanned leather.
[0043] It was determined that the chloride ion concentration in the tanning wastewater in this embodiment was 0.2 g / L, the shrinkage temperature of the crust leather was 98.2°C, the softness was 8.4 mm, and the tensile strength was 17.2 N / mm 2 , tear strength is 53.8N / mm; after heat aging, the shrinkage temperature of the leather is 98.0℃, the softness is 8.3mm, and the tensile strength is 17.1N / mm 2 , the tear strength is 52.8N / mm.
[0044] Example 4 Add 40wt% water and 1wt% sodium dialdehyde carboxymethyl cellulose based on the weight of the limed bare hide to the softened cowhide, and after penetration for 360min, combine at 35℃ for 30min. Then, adjust the pH of the bath to 2.5 in a salt-free state. Then, change the bath, add 200wt% water, 5wt% ferric nitrate and 8wt% sodium citrate, and after penetration for 60min, extract the alkali to pH 4.0, combine at 42℃ for 180min, and stand overnight to obtain iron tanned leather.
[0045] It was determined that the chloride ion concentration in the tanning wastewater in this embodiment was 0.2 g / L, the shrinkage temperature of the crust leather was 85.4°C, the softness was 7.4 mm, and the tensile strength was 16.2 N / mm 2 , tear strength is 49.7N / mm; after heat aging, the shrinkage temperature of the leather is 84.9℃, the softness is 7.4mm, and the tensile strength is 16.1N / mm 2 , the tear strength is 49.2N / mm.
[0046] Example 5 Add 120wt% of water and 3wt% of dialdehyde carboxymethyl starch to the softened sheepskin based on the weight of the limed bare skin, and after infiltration for 180min, combine at 42°C for 240min. Then, adjust the pH of the bath to 3.2 in a salt-free state. Then, change the bath, add 40wt% of water, 16wt% of iron sulfate and 4wt% of sodium formate, and after infiltration for 180min, extract the alkali to pH 3.5, combine at 38°C for 120min, and stand overnight to obtain iron tanned leather.
[0047] According to the measurement, the chloride ion concentration in the tanning wastewater in this embodiment is 0.2g / L, the shrinkage temperature of the crust leather is 96.7℃, the softness is 8.7mm, and the tensile strength is 12.9N / mm 2 , tear strength is 41.5N / mm; after heat aging, the shrinkage temperature of the leather is 95.9℃, the softness is 8.6mm, and the tensile strength is 12.8N / mm 2 , the tear strength is 40.4N / mm.
[0048] Example 6 Add 40wt% water and 1wt% sodium dialdehyde carboxymethyl cellulose based on the weight of the limed bare hide to the softened goat, infiltrate for 30 minutes, and combine at 38°C for 120 minutes. Then, adjust the pH of the bath to 2.5 in a salt-free state. Then, change the bath, add 120wt% water, 16wt% ferric nitrate, 4wt% sodium formate and 4wt% sodium tartrate, infiltrate for 180 minutes, extract alkali to pH 4.0, combine at 35°C for 60 minutes, and stand overnight to obtain iron tanned leather.
[0049] According to the measurement, the chloride ion concentration in the tanning wastewater in this embodiment is 0.2g / L, the shrinkage temperature of the crust leather is 92.9℃, the softness is 8.2mm, and the tensile strength is 18.3N / mm 2 , tear strength is 55.6N / mm; after heat aging, the shrinkage temperature of the leather is 92.5℃, the softness is 8.1mm, and the tensile strength is 18.2N / mm 2 , the tear strength is 54.8N / mm.
[0050] Example 7 Add 200wt% of water and 5wt% of dialdehyde carboxymethyl starch based on the weight of the limed bare hide to the softened cowhide, and after infiltration for 30 minutes, combine at 38°C for 120 minutes. Then, adjust the pH of the bath to 4.0 in a salt-free state. Then, change the liquid, add 120wt% of water, 30wt% of ferric nitrate, 0.5wt% of sodium lactate and 0.5wt% of sodium citrate, and after infiltration for 300 minutes, extract the alkali to the pH of the bath to 3.5, combine at 35°C for 60 minutes, and stand overnight to obtain iron-tanned leather.
[0051] According to the measurement, the chloride ion concentration in the tanning wastewater in this embodiment is 0.2g / L, the shrinkage temperature of the crust leather is 97.3℃, the softness is 8.3mm, and the tensile strength is 13.9N / mm 2 , tear strength is 44.7N / mm; after heat aging, the shrinkage temperature of the leather is 96.8℃, the softness is 8.2mm, and the tensile strength is 13.6N / mm 2 , the tear strength is 43.9N / mm.
[0052] Example 8 Add 200wt% of water and 5wt% of sodium dialdehyde alginate based on the weight of the limed bare skin to the softened sheepskin, and after penetration for 360min, combine at 35°C for 360min. Then, adjust the pH of the bath to 4.0 in a salt-free state. Then, change the bath, add 200wt% of water, 30wt% of iron sulfate, 4wt% of sodium tartrate and 4wt% of sodium citrate, and after penetration for 60min, extract the alkali to pH 4.0, combine at 42°C for 180min, and stand overnight to obtain iron tanned leather.
[0053] It was determined that the chloride ion concentration in the tanning wastewater in this embodiment was 0.2 g / L, the shrinkage temperature of the crust leather was 98.4°C, the softness was 9.1 mm, and the tensile strength was 12.6 N / mm 2 , tear strength is 40.4N / mm; after heat aging, the shrinkage temperature of the leather is 98.3℃, the softness is 8.9mm, and the tensile strength is 12.4N / mm 2 , the tear strength is 40.1N / mm.
[0054] Example 9 Add 120wt% water and 3wt% dialdehyde carboxymethyl starch based on the weight of the limed bare hide to the softened goat leather, and after infiltration for 180min, combine at 42℃ for 240min. Then, adjust the pH of the bath to 3.2 in a salt-free state. Then, change the bath, add 40wt% water, 5wt% ferric nitrate, 2wt% sodium lactate and 2wt% sodium tartrate, and after infiltration for 300min, add alkali to the bath pH 4.5, combine at 38℃ for 120min, and stand overnight to obtain iron tanned leather.
[0055] According to the measurement, the chloride ion concentration in the tanning wastewater in this embodiment is 0.2g / L, the shrinkage temperature of the crust leather is 90.1℃, the softness is 7.9mm, and the tensile strength is 20.1N / mm 2 , tear strength is 58.4N / mm; after heat aging, the shrinkage temperature of the leather is 89.9℃, the softness is 7.8mm, and the tensile strength is 19.9N / mm 2 , the tear strength is 57.8N / mm.
[0056] Example 10 Add 120wt% water and 3wt% sodium dialdehyde carboxymethyl cellulose based on the weight of the limed bare hide to the softened cowhide, and after infiltration for 180min, combine at 42°C for 240min. Then, adjust the pH of the bath to 3.5 in a salt-free state. Then, change the liquid, add 120wt% water, 16wt% iron sulfate, and 4wt% sodium tartrate, and after infiltration for 180min, extract the alkali to the pH of the bath to 4.0, combine at 38°C for 120min, and stand overnight to obtain iron tanned leather.
[0057] According to the measurement, the chloride ion concentration in the tanning wastewater in this embodiment is 0.2g / L, the shrinkage temperature of the crust leather is 94.9℃, the softness is 8.2mm, and the tensile strength is 14.8N / mm 2 , tear strength is 46.1N / mm; after heat aging, the shrinkage temperature of the leather is 94.7℃, the softness is 8.0mm, and the tensile strength is 14.5N / mm 2 , the tear strength is 45.9N / mm.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A salt-free and chrome-free tanning method, characterized in that: Using softened bare hides as raw materials, bio-based dialdehyde carboxylic acid pre-tanning, salt-free pickling and iron salt tanning are carried out in sequence; Wherein, based on the weight of the limed bare skin, the added amount of the bio-based dialdehyde carboxylic acid is 1wt%-5wt%; the added amount of the iron salt is 5wt%-30wt%.
2. The salt-free and chrome-free tanning method according to claim 1, characterized in that: The softened bare hide comprises any one of softened sheep hide, softened goat hide and softened cow hide.
3. The salt-free and chrome-free tanning method according to claim 1, characterized in that: The bio-based dialdehyde carboxylic acid comprises any one of dialdehyde sodium alginate, dialdehyde sodium carboxymethyl cellulose and dialdehyde carboxymethyl starch.
4. The salt-free and chrome-free tanning method according to claim 1, characterized in that: The bio-based dialdehyde carboxylic acid pre-tanning is performed by infiltrating the raw material with the bio-based dialdehyde carboxylic acid for 30-360 minutes and then combining the raw material at 35-42° C. for 30-240 minutes.
5. The salt-free and chrome-free tanning method according to claim 1, characterized in that: The salt-free pickling is to adjust the pH of the reaction solution to 2.5-4.0 without using sodium chloride.
6. The salt-free and chrome-free tanning method according to claim 1, characterized in that: The iron salt comprises iron sulfate or iron nitrate.
7. The salt-free and chrome-free tanning method according to claim 1, characterized in that: The iron salt tanning is to use iron salt to penetrate the pre-tanned raw materials for 60-300 minutes, add alkali to pH 3.5-4.5, and combine at 35-42° C. for 60-180 minutes.
8. The salt-free and chrome-free tanning method according to claim 7, characterized in that: The iron salt tanning process also contains a ligand, which includes any one or more of sodium formate, sodium lactate, sodium tartrate and sodium citrate.
9. The salt-free and chrome-free tanning method according to claim 7, characterized in that: The alkali extracting agent used in the alkali extracting comprises any one or more of sodium bicarbonate, sodium carbonate, magnesium oxide and automatic alkali extracting agent.
10. Tanned leather obtained by the salt-free and chrome-free tanning method as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Organic metal complex tanning agent and preparation method thereof
CN104862431A
No-pickling chrome-free tanning process based on multi-metal cooperation tanning agent
CN107201414A
Building integrated system with increased ease of selection
KR102396257B1